Gender Based Prevalence of Health Risk Behaviours among Adolescents in Ofu Local Government Area, Kogi State - Idache, Benjamin Mudi; Moses, Folusayo Adeola; Adams, David (International Journal of Human Kinetics, Health and Education, 2022)
The study investigated gender based prevalence of health risk behaviours among adolescents in Ofu local government area of Kogi State. The study was guided by three specific purposes and three research questions. A descriptive survey research design was adopted for the study and multistage sampling procedure was used to draw 1,920 adolescents from 960 households scattered throughout the eight wards in Ofu Local Government Area, Kogi State. A self structured questionnaire was used for data collection. Data collected were subjected to statistical analysis using descriptive statistics of frequency count, percentage, mean and standard deviation. Findings revealed that substance abuse was prevalent in the study area. Physical inactivity and unsafe sexual behaviour were not prevalent among adolescents. However, awareness should be created among parents and community members by the media to bring about behavioural changes in terms of alcohol consumption, smoking, sexual activities, healthy dietary habits, physical violence and physical activity practiced by the students.